PENDAMPINGAN PENGOLAHAN TAHU WALIK “ENAK DAN GURIH” DESA GODAN - Syamsul Hadi; Adinda Khaerani; Dania Putri Ramadhani; Gideon Radinal; Hanifarif Rafi Rizaldy; Hasna Khairunnisa; Karina Anastasya Putri; Khafid Alfian Rosyadi; Ni’matus Sholikah; Syafa Putri Innasia (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Economic developments in regions in Indonesia have changed, mainly due to the Covid-19 pandemic, one of which is the impact on MSMEs. Some MSMEs are even forced to stop because production cannot be carried out, and restrictions from the government hamper buying and selling activities. Therefore, at this time, MSMEs, which were previously constrained by the Covid-19 pandemic, are starting to try to bounce back. Godan Village is one of the villages in Grobogan Regency that seeks to improve the economy by reviving MSMEs. With this, the UNS 358 KKN Team carried out community service activities by carrying out the main work program entitled Assistance in processing tahu walik. This activity is carried out offline in conjunction with implementing the Monthly PKK in Godan Village. This activity went well and received a positive response from PKK members who attended the training. PKK members are also enthusiastic about producing the tahu walik on a home scale. This assistance activity for processing tahu walik is very beneficial for the people of Godan Village, especially for people with MSMEs.